2021
DOI: 10.1007/s11069-021-04634-8
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling of real-time coastal flooding predictions for decision support

Abstract: During coastal storms, forecasters and researchers use numerical models to predict the magnitude and extent of coastal flooding. These models must represent the large regions that may be affected by a storm, and thus, they can be computationally costly and may not use the highest geospatial resolution. However, predicted flood extents can be downscaled (by increasing resolution) as a post-processing step. Existing downscaling methods use either a static extrapolation of the flooding as a flat surface, or rely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This result is visually confirmed by observing that the green FP area is larger than the red FN area, as shown in Figure 12. Previous studies have also shown that static methods tend to overpredict flood inundation (Ramirez et al, 2016;Didier et al, 2019;Rucker et al, 2021;Li et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This result is visually confirmed by observing that the green FP area is larger than the red FN area, as shown in Figure 12. Previous studies have also shown that static methods tend to overpredict flood inundation (Ramirez et al, 2016;Didier et al, 2019;Rucker et al, 2021;Li et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…We neglect the other bank across from the coast, which is analogous to another continent or island. The ocean water surface elevation is extended horizontally from the ocean surface to the landscape topography, taking an approximate but computationally efficient approach that can be referred to as "bathtub," "equilibrium," or "static" (Gallien et al, 2011;Rucker et al, 2021). We apply a static equilibrium assumption to the water surface, assuming that the water surface is absolutely motionless and horizontal, similar to the water surface of a still bathtub (Figure 8).…”
Section: C-handmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupled ADCIRC+SWAN model is previously validated in terms of its long-term impact on storm surge on the Gulf coast [15][16][17]. Inland inundation modeling requires a small, fine resolution finite element domain to capture flood water behavior over small-sized land features [18]. This smaller domain is nested within the larger coupled model domain as performed in a number of studies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%